As avenidas da metrópole, as ruas do lugar: produção social do espaço a partir das transformações da Lagoinha e da Avenida Presidente Antônio Carlos (Belo Horizonte, MG) - Daila Coutinho Araujo (2016)
The avenues and streets of a city represent more than just sites designated to circulation of vehicles, pedestrians and goods: they are crucial in the social production of urban space process. In the first part of this research, we approach the avenue to the spatial dimension defined by Henri Lefebvre as conceived space, result of a technicist, bureaucratic and rational urban planning distant from the near order and therefore abstract. We highlight its role in the constitution of the metropolis oriented by two elements: the plan, in which the urban plan of Belo Horizonte is presented as a symbol of a modernization project alienated to social reality; and avenues, bringing forward the avenues of the plan as elements of articulation of order and progress ideals, and dictating the urban expansion to north and west directions giving evidence of a metropolitan setting. In the end of the first part, we present the reconstruction and remodeling projects of President Antônio Carlos Avenue as deep scars in the city space especially in the traditional neighborhood of Lagoinha. In the second part, we are oriented by the comprehension that, despite the abstraction of the conceived space of the avenues, the city may be appropriated with other senses through the lived space. We use as guiding elements: streets, which establish their urbanity as they become locus of the encounter, the party, the celebration of differences and also of everyday life with its inherent contradictions and alienation; and the lived space, presenting the neighborhood of Lagoinha from the appropriations of its spaces (the streets, but also the President Antônio Carlos Avenue) as a sense of place and artwork. In the appropriation process as a place, the experiences of the dwellers are responsible for the construction of meanings and identities in a subjective level. In the appropriation as an artwork, the signification processes refer to the proposals of its authors. Thus, if everyday life is a time of alienation consisted from the dull repetition of the everyday life events, it is through it that the creative appropriations of the space occur. Through a shared practice centered on the value of use and everydayness (the everyday life not driven by consumption values), the urban praxis arises as a reflexive and not alienated practice. The urban revolution desired by Lefebvre could happen, then, through the modifications in everyday life aimed to the creation of artworks and places.